Managed Claims: Zur Notwendigkeit einer vertikalen Integration von Versicherungs- und Reparaturleistungen - Martin Nell (Hamburg University, Institute for Risk and Insurance, 2001)
The paper deals with the so called external moral hazard. This problem occurs, when-ever insurance companies bear the repair costs of the insured in the case of a damage. The insurance coverage results in a decrease of the price elasticity of demand and therefore in higher prices for repair services and goods, since markets for repair goods are usually imperfect and prices are thus above marginal costs. Empirical evidence is given that the price increase for repair services and goods due to external moral hazard is quite substantial. It is argued in this paper that the only way to tackle external moral hazard efficiently is a vertical integration of insurance on the one hand and the supply of repair goods and services on the other hand: Insurance companies have either to provide repair goods and services by themselves or make cooperation agreements with providers.
Keywords: 330